(untitled) (American Journal of Islam and Society, 2022)
Emad Hamdeh’s Salafīsm and Traditionalism: Scholarly Authority in Modern Islam is a meticulous study of a contemporary debate about scholarly legitimacy, between the Salafī hadith-scholar Nāṣir al-Dīn al-Albānī and his traditional Sunnī interlocutors, focused on disputes over both hadiths and Islamic Law (fiqh). The book is a welcome addition to contemporary studies about Salafīsm, which (as the author observes) often tend to focus on political dimensions of the movement, at the expense of religious elements—this although the latter may be more significant in the sense that most Salafīs themselves view their initiative as primarily religious, and not necessarily political.